Tourists’ Perceptions of Public Information Signage in Lombok Tourism Destinations: A Linguistic Landscape Study - Rahma Dewi Hartati; Brillianing Pratiwi; Arini Noor Izzati; Juliana Simangunsong (Bale Literasi: Lembaga Riset, Pelatihan & Edukasi, Sosial, Publikasi, 2026)
This study aims to examine tourists’ perceptions of language use on public information signs in tourism destinations across Lombok, Indonesia. A descriptive quantitative approach was employed, and data were collected through a questionnaire-based survey involving 164 respondents. Of these, 100 respondents who had visited Lombok were included in the main analysis. Data were analyzed through three stages: 1) descriptive statistical analysis using frequencies and percentages, 3) data visualization, and 3) interpretation based on linguistic signs as highly useful for understanding tourism environments and navigating destinations. The linguistic landscape features most frequently noticed by tourist include shop and restaurant signs, directional signs, and promotional banner. The results also reveal that bilingual (Indonesia-English) and multilingual signage plays an important role in improving information accessibility and supporting communication among diverse visitor groups. Furthermore, multilingual signs incorporating local languages contribute not only to the informational function of public signage but also to the representation of local cultural identity. These findings highlight the informational and symbolic functions of linguistic landscapes in tourism settings. This study recommends the implementation of multilingual public signage that integrates local, national, and international languages, supported by visually appealing designs that reflect local culture. Such an approach may enhance communication effectiveness, strengthen cultural representation, and improve tourists’ experiences in Lombok tourism destinations.